Inhibitory effect of taspine derivative TAD1822-7 on tumor cell growth and angiogenesis via suppression of EphrinB2 and related signaling pathways - Liu Rui; Yu Runze; Cui Yuxin; Fan Mengying; Wang Bo; Zhang Yanmin (Acta Pharmaceutica)
The aim of this study was to investigate the inhibitory effect of TAD1822-7, a synthesized taspine derivative, on cancer through its effects on tumor cell growth and angiogenesis via suppression of EphrinB2. The obtained data showed that TAD1822-7 decreased Bel-7402 cell viability and colony formation ability and suppressed cell migration. TAD1822-7 effectively inhibited blood vessel formation in an aortic ring assay to examine angiogenesis. Moreover, it also down regulated the expression of VEGFR2, VEGFR3, CD34, PLCγ, Akt, MMP2, MMP9, and CXCR4, and suppressed the expression of EphrinB2 and its PDZ protein, PICK1, in Bel-7402 cells. These results indicate that TAD1822-7 is a potential anti-angiogenic agent that can inhibit the viability and migration of Bel-7402 cells via suppression of EphrinB2 and the related signaling pathways.